Feminist and LGBTI+ Activism across Russia, Scandinavia and Turkey Transnationalizing Spaces of Resistance - Çağatay, Selin (Thinking Gender in Transnational Times, 2022)
What do struggles for women's and LGBTI+ rights in Russia, Turkey and the Scandinavian countries have in common? And what can actors who struggle for rights and justice in these contexts learn from each other? Based on a multisited ethnography of feminist and LGBTI+ activisms across Russia, Turkey and the Scandinavian countries, this Open Access book explores transnational struggles on various levels, from the micro-scale of the everyday to large-scale, spectacular events. Drawing on ethnographic insights and encounters from various sites, this book conceptualizes resistance as situated in the grey zone between barely perceptible, even hidden or covert, forms of mundane activist practices and highly visible street protests, gathering large crowds. Taking the reader beyond the dichotomies of visible/invisible and public/private, this book advances new understandings of resistance, solidarity, and activism in transnationalizing feminist and queer struggles, illustrated by rich ethnographic case studies from Russia, Scandinavia and Turkey.